2009
DOI: 10.1097/jcn.0b013e3181b85c7b
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism

Abstract: Venous thromboembolism (VTE) is a major cause of death and disability throughout the world. Evidenced-based guidelines and performance measures aimed at prevention of VTE have existed for over a decade, yet VTE occurrence rate appears to be increasing. This increase may, in part, be due to more aggressive surveillance; however, noncompliance with guideline recommendations for prophylaxis is a concern. Several barriers have been identified as contributing to lack of guideline adherence including lack of support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Other multifaceted intervention studies focusing on antibiotics found an increase in the rate of guideline adherence of antibiotic prescription [ 27 , 28 ]. The hypothesis that a multifaceted approach is the most effective method to improve protocol adherence is supported by a previous study of Worel et al [ 11 ] who described that lack of audit tools and feedback systems and the presence of an abundance of guidelines with conflicting recommendations result in lack of guideline adherence. Furthermore, passive dissemination of guidelines alone is often insufficient to have a positive impact on guideline adherence [ 13 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other multifaceted intervention studies focusing on antibiotics found an increase in the rate of guideline adherence of antibiotic prescription [ 27 , 28 ]. The hypothesis that a multifaceted approach is the most effective method to improve protocol adherence is supported by a previous study of Worel et al [ 11 ] who described that lack of audit tools and feedback systems and the presence of an abundance of guidelines with conflicting recommendations result in lack of guideline adherence. Furthermore, passive dissemination of guidelines alone is often insufficient to have a positive impact on guideline adherence [ 13 ].…”
Section: Discussionmentioning
confidence: 91%
“…Studies evaluating partial and/or complete compliance with the American College of Chest Physicians (ACCP) venous thromboembolism (VTE) prevention guidelines, published between 2005 and 2008, showed that compliance rates ranged from 2.8 to 84% [ 11 ]. Proietti and colleagues assessed adherence in a cohort of atrial fibrillation (AF) acutely admitted patients.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in educational levels, inadequate resources, job discontent, lack of drive, and a smaller extent of higher training are some of the issues that play to barriers, as per Asemahagn (2014). Additionally, lack of enabling mechanisms, individual responsibility for implementation, lack of acceptance, perceived lack of necessity in particular therapeutic areas, lack of oversight or incentives, and contradicting guideline directions have all been noted as hurdles to guideline adherence (Worel, 2009).…”
Section: Discussionmentioning
confidence: 99%